Disability Prediction by Early Hammersmith Neonatal Neurological Examination: A Diagnostic Study. (October 2020) - Venkata, Sujith Kumar Reddy Gurram; Pournami, Femitha; Prabhakar, Jyothi; Nandakumar, Anand; Jain, Naveen
Background and Objectives: Hammersmith Neonatal Neurologic Examination (HNNE) is used to identify term and preterm infants at risk of neurodevelopmental disability. The test is recommended at corrected term age in preterm; and around 2 weeks postnatal age in term neonates. As the current trend is to discharge based on physiological stability, it may not be feasible to perform HNNE at recommended age. The authors investigated whether predictive ability of the test for neurodevelopmental disability remained unchanged if performed early (before discharge). Methods: The authors enrolled preterm and at-risk term neonates. HNNE PE was performed before discharge in all infants. The test was repeated in preterm infants at 40 weeks postmenstrual age and in term neonates at 2 weeks of age (HNNE RA). Neurodevelopmental disability was assessed at 1 year of age. Results: HNNE PE was done in 125 neonates (103 preterm, 22 term neonates). HNNE RA was done in 58% infants. Neurodevelopmental disability was assessed in 84 (67%) of infants. Neurodevelopmental disability was noted in 14/84 (16.6%) babies. The receiver operating characteristic curve of raw scores showed that area under the curve for HNNE PE (0.71) and HNNE RA (0.66) were similar. The sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, and negative likelihood ratio for both the tests were similar for a cutoff optimality score of 32.5. HNNE PE could be performed up to 4 weeks earlier than HNNE RA with the same predictive ability for neurodevelopmental disability. Conclusions: HNNE PE was as reliable as HNNE RA in predicting neurodevelopmental disability at 1 year of age. Completion of the test is assured and provides several weeks lead time for early intervention.